A multi-stakeholder perspective on corporate social responsibility: The case of Zoomarine Algarve - Contreiras, J.P.; Machado, V.; Duarte, A.P. (3rd Symposium on Ethics and Social Responsibility Research, 2015)
The study here presented is part of a larger research project on sustainable tourism and corporate social responsibility (CSR) and allowed to characterize the CSR practices of an organization based on the perspective of three different internal and external stakeholders – employees, visitors and local community members. A sample of 405 individuals participated in the study, answering to a voluntary survey. Results revealed that the three stakeholder groups were aligned in their perceptions, considering that the company is engaged in CSR, has a good corporate image, provides a service with quality and generates positive contributions for community both in economic and non-economic domains. Employees tended to judged even more positively the set of practices under appreciation indicating a high identification with the organization.